PROMOTING PEACEFUL CLASSROOMS THROUGH A SPIRITUAL COMMUNICATION MODEL FOR ISLAMIC SCHOOLS - Fa'atin, Salmah - (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
Communication is essential in learning activities. Communication should be the main medium in creating positive emotions in the classroom. Therefore, the learning communication model needs to be continuously developed so that classroom communication becomes effective and has an impact on positive changes in students' behavior. This article aims to develop an Edusufistic communication model to create positive emotions in Islamic educational institutions. This paper is a mix of qualitative and quantitative research. Centralized group discussion (FGD) activities, observations, direct interviews, and questionnaires were used with 27 Indonesian participants and 26 Malaysian participants. The results of this study revealed that the image of communication in the classroom is still rigid, unidirectional, resulting in communication. This leaves many emotional problems for teachers and students. Edusufistic communication model has been recognized by educators to be able to revitalize the practice of learning communication that has been practiced so far. Edusufistic communication brings positive climate and emotions in the classroom, empathic, sympathetic and loving. This study also reveals the emotional impact of the Edusufistic model on the peace of mind of educators and students. From the results of the quantitative data analysis, the educators' perceptions show that the implementation of the Edusufistic Communication Model does not find many obstacles. The results of this study are expected to be a recommendation for policy makers to provide full socialization of the Edusufistic communication model for educators at different levels.